Original paperMalignant obstructive jaundice – brachytherapy as a tool for palliation - Jain, Sandeep; Kataria, Tejinder; Bisht, Shyam Singh; Gupta, Deepak; Vikraman, Subramani; Baijal, Sanjay; Sud, Randhir (Journal of Contemporary Brachytherapy, 2013)
Purpose : Malignant obstructive jaundice (MOJ) is relieved by stenting via endoscopic retrograde cholangiopancreatography (ERCP) or percutaneous transhepatic cholangiography and biliary drainage (PTCD). Stent occlusion rates of 30-45% have been reported in literature due to tumor ingrowth or overgrowth. We prospectively evaluated the feasibility and the role of intraluminal brachytherapy (ILBT) in preventing stent blockage in patients with MOJ after PTCD and stenting. Material and methods : Twelve patients with MOJ who underwent PTCD followed by self expanding metallic stent (SEMS) placement were prospectively enrolled in this study. Written informed consent was obtained. Intraluminal brachytherapy was done once patient was stable and serum bilirubin was less than 2 mg% or 50% of baseline value. On the day of ILBT, 6 French brachytherapy catheters were placed across malignant stricture under fluoroscopic guidance with placement of the tip 1 cm distal to stricture. A dose of 10 to 14 Gy was delivered at 1 cm from central axis of the source. Suitable patients also received external beam radiotherapy (EBRT) with weekly concurrent chemotherapy. Results: All patients tolerated the procedure well with minimal acute and late toxicities. Duodenal ulceration was observed in 1 patient. At a mean follow up of 10.25 months (5-24 months), stents were patent in 10/12 subjects and stent patency duration of 9.8 months (5-22) was reported. Conclusions : Intraluminal brachytherapy post PTCD is feasible and effective in preventing stent occlusion with minimal acute and late toxicities.